A Dog's Way Home - Olmos, Edward James; Judd, Ashley; Hauer-King, Jonah; 1995-; Bauer, Chris; Studi, Wes; Cameron, W. Bruce; 1981; Shipp, Alexandra; Howard, Bryce Dallas; Smith, Charles Martin; Michon, Cathryn; et al. (Culver City, California, 2019)
As a puppy, Bella finds her way into the arms of Lucas, a young man who gives her a good home. When Bella becomes separated from Lucas, she soon finds herself on an epic, 400-mile journey to reunite with her beloved owner. Along the way, the lost but spirited dog touches the lives of an orphaned mountain lion, a down-on-his-luck veteran and some friendly strangers who happen to cross her path.
MPAA rating: PG; for thematic elements, some peril and language
CHV rating: PG; not recommended for young children, violence, frightening scenes.
Keywords: Juvenile films; Juvenile films; Voyages and travels; Dogs; Drama; Voyages and travels; Drama; Dogs; Drama; Feature films; Video recordings for people with visual disabilities; Video recordings for the hearing impaired; Drama; Childrens films; Feature films; Fiction films; Video recordings for people with visual disabilities; Film adaptations; Childrens films; Video recordings for the hearing impaired; Animal films